The Linguistic Landscape of Popular Culture: Analyzing Military Speech in Manga - Ioana Ruxandra Toșu (Linguaculture)
This study investigates Japanese popular culture, focusing on manga as a central cultural product that offers rich narrative and visual content that reflects both universal and culturally specific themes. One key concept explored in this study is yakuwarigo, or “role language”, a linguistic phenomenon where specific speech patterns convey a character’s social role, age, gender, or personality. Yakuwarigo serves as a tool for character development, allowing readers to infer traits through language. The research includes a pragma-linguistic analysis of yakuwarigo in manga, focusing on the speech of military leaders. Using Erwin Smith’s communication acts from Shingeki no Kyojin (‘Atacul titanilor’) as a case study, the analysis examines how his speech patterns shift between formal, honorific language when addressing superiors and direct, motivational language with subordinates. This duality highlights the adaptability and strategic clarity of his role as a leader. The study also evaluates the Romanian translations of his addresses, assessing how effectively they retain the original pragmatic and linguistic nuances, thus contributing to the understanding of cultural and linguistic transfer in manga translations.